Odpowiedź :
a) 3(x-4) = 16 +2x
3x - 12 = 16 + 2x
3x - 2x = 16 + 12
x = 28
b) [tex]\frac{1}{4}(3x+1) - 2 = 2x - 5[/tex]
[tex]\frac{3}{4}x + \frac{1}{4}-2 = 2x-5[/tex]
[tex]\frac{3}{4}x - \frac{7}{4} = 2x - 5[/tex] /*4
3x-7= 8x - 20
3x - 8x = 20 + 7
-5x = -13 /:(-5)
x = [tex]\frac{13}{5}[/tex]
x = [tex]2\frac{3}{5}[/tex]
a)
[tex]3(x-4) = 16+2x\\\\3x-12 = 16 + 2x\\\\3x-2x = 16+12\\\\\boxed{x = 28}[/tex]
b)
[tex]\frac{1}{4}(3x+1)-2 = 2x-5 \ \ |\cdot4\\\\4\cdot\frac{1}{4}(3x+1)-4\cdot2 = 4(2x-5)\\\\3x+1 - 8 = 8x-20\\\\3x-7 = 8x - 20\\\\3x-8x = -20+7\\\\-5x = -13 \ \ |:(-5)\\\\x = \frac{13}{5}\\\\\boxed{x = 2\frac{3}{5}}[/tex]